2016
DOI: 10.1039/c5ra23019e
|View full text |Cite
|
Sign up to set email alerts
|

Polyelectrolyte multilayer film modification for chemo-mechano-regulation of endothelial cell response

Abstract: The new multilayer polyelectrolyte films (PEMs) that are able to simulate the structure and functions of the extracellular matrix have become a powerful tool for tailoring biointerfaces of “cardiovascular” implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The surface roughness of the PEM was determined after its structure was stabilized by nanoparticles. It has been noticed that the introduction of graphene oxide flakes (average size: 5.0 ± 2.0 nm [ 16 ]) resulted in a significant decrease of roughness ( Figure 2 b,c). The surface morphology of PEMs loaded with silver nanoparticles (average size: single particle 5.0 ± 1.2 nm; aggregate 40.6 ± 4.5 nm [ 16 ]) was determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness of the PEM was determined after its structure was stabilized by nanoparticles. It has been noticed that the introduction of graphene oxide flakes (average size: 5.0 ± 2.0 nm [ 16 ]) resulted in a significant decrease of roughness ( Figure 2 b,c). The surface morphology of PEMs loaded with silver nanoparticles (average size: single particle 5.0 ± 1.2 nm; aggregate 40.6 ± 4.5 nm [ 16 ]) was determined.…”
Section: Resultsmentioning
confidence: 99%
“…It has been noticed that the introduction of graphene oxide flakes (average size: 5.0 ± 2.0 nm [ 16 ]) resulted in a significant decrease of roughness ( Figure 2 b,c). The surface morphology of PEMs loaded with silver nanoparticles (average size: single particle 5.0 ± 1.2 nm; aggregate 40.6 ± 4.5 nm [ 16 ]) was determined. These coatings had significantly lower roughness than the unmodified films without nanoparticles ( Figure 2 b,c).…”
Section: Resultsmentioning
confidence: 99%
“…To further increase the elastic modulus, the surface of the PEM can be modified; for instance, gold nanoparticles have been incorporated into HA/PLL PEMs, and it was found that the particles accumulated on the surface of the film and drastically increased the surface elastic modulus to a maximum of 1.3 MPa from 80 kPa [ 182 ]. Further surface modifications upon HA/PLL PEMs were performed by Mzyk et al (2016) [ 183 ], in which, in combination with GnP or 400 mM EDC/NHS, silicon carbide nanoparticles were incorporated into the PEM, giving elastic moduli of 760 and 830 kPa, respectively (increased from ~10 kPa for native PEMs). Ag nanoparticles were also incorporated and showed an increase in the elastic modulus compared to native films, but showed no such drastic increase when compared to GnP cross-linked films (213 kPa and 214 kPa, respectively), but when used in combination with 400 mM EDC/NHS, the elastic modulus was raised to ~237 kPa.…”
Section: Biopolymer Dynamics At the Macroscalementioning
confidence: 99%
“…* represents p < 0.05 vs. non-cross-linked sample with graphene flakes; ** represents p < 0.05 vs. non-cross-linked sample with SiC; *** represents p < 0.05 vs. non-cross-linked sample with Ag; **** represents p < 0.05 vs. non-cross-linked sample without nanoparticles. Figure taken from reference [ 183 ], C opyright © 2020 Royal Society of Chemistry.…”
Section: Figurementioning
confidence: 99%
“…The shell can be modified for cell specific interaction by functionalising multilayers with peptides, proteins, nucleic acids (e.g., DNA, RNA, etc.) [ 177 ] and metal nanoparticles (NPs) (e.g., gold NPs) [ 178 , 179 ] as the ligands themselves or additives that are bound to specific ligands. These ligands can interact at specific sites (receptors) at the targeted cell and potentially lead to the internalisation of the capsules inside the targeted cell, that is typically driven by endocytosis.…”
Section: Applications Of Pemcs As Delivery Carriersmentioning
confidence: 99%